Liver and Intestine Transplantation in the United States, 1995–2004 - Shiffman, M. L.; Saab, S.; Feng, S.; Abecassis, M. I.; Tzakis, A. G.; Goodrich, N. P.; Schaubel, D. E. (American journal of transplantation, 2006)
Three years of survival data are now available and the impact of the model for end‐stage liver disease (MELD) allocation system is becoming clear. After a decline in new registrants to the waiting list in 2002, the number increased to 10 856 new patients in 2004. Since the implementation of MELD, the percentage of patients who have been on the list for 1–2 years has declined from 24% to 19%. There has been a shift upward in the percentage of patients with higher MELD scores on the waiting list. An increasing percentage of adult living donor liver recipients are over the age of 50 years; from 1% in 1997 to 51% in 2004. Parents donating to children (93% of living donors in 1995), represented only 14% in 2004. Long‐term adjusted patient survival declined with increasing recipient age in adults following either DDLT or LDLT. Cirrhosis caused by chronic hepatitis C virus (HCV) is the leading indication for liver transplantation and is associated with reduced long‐term survival in recipients with HCV compared to those without HCV, 68% at 5 years compared to 76%. Although the intestine waiting list has more than doubled over the last decade, an increasing number of centers now perform intestinal transplantation with greater success.